Characterization and Epidemiology of Pigeon Paramyxovirus Type-1 Viruses (PPMV-1) Isolated in Macedonia - Aleksandar Dodovski; Iskra Cvetkovikj; Kiril Krstevski; Ivancho Naletoski; Vladimir Savić (American Association of Avian Pathologists, 2017)
We have characterized in this study 10 PPMV-1 isolated from domestic pigeons and one PPMV-1 isolated from a feral pigeon in the period 2007–2012, using both classical methods (HI test and ICPI test) and molecular methods (RT-qPCR, RT-PCR, and nucleotide sequencing). Using phylogenetic analysis of partial fusion gene sequences, these viruses clustered with recent European PPMV-1 isolates (EU/re) within the genotype VIb/1. All isolates possessed virulent cleavage site motifs with variable morbidity and mortality in pigeons. The intracerebral pathogenecity indices of the five isolates ranged from 0.59 to 1.53. The repetitive isolation of PPMV-1 viruses for several consecutive years led toward establishing enzootic presence of the disease in pigeons. A high nucleotide sequence homology between the Macedonian isolates and EU/re isolates was shown. Co-circulation of different isolates in the same holdings was detected. This is the first study to extensively describe the molecular epidemiology of PPMV-1 isolated in Macedonia.
Keywords: pigeon paramyxovirus type 1, pigeon, characterization, phylogeny, epidemiology, Macedonia